EVALUASI IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN PENJAS-ORKES DI SD NEGERI INTI 4 KECAMATAN MEMPAWAH HILIR KABUPATEN MEMPAWAH - Tri Liana; Aloysius Mering; Indri Astuti (Universitas Tanjungpura, 2021)
AbstractThis study aims to find out curriculum 2013 implementation, describe the constraints faced in the implementation of the curriculum 2013 and the strategy used in the implementation 2013 curriculum program in the field or orchestra education in inti 4 public elementary school Mempawah downstream. This study is an evaluation research using the CIPP (Contex, Input, Process and Product) developed by Stufflebeam, with the research subjects being core 4 elementary schools consisting of 4 public elementary school. Data was obtained through curriculum expert validation questionnaires, observation and interviews. Data analysis was carried out qualitatively. The results of the study show that the implementation of the 2013 curriculum has largely gone smoothly. The obstacies faced in the implementation of the 2013 curriculum were the lamitations of orchestra teacher in the school and the limited facilities and infrastructure to support practical activities and the lack of other supporting facilities. The strategy to overcome the obctacles in the 2013 curriculum implementation that needs to be prepared furthur is to make good planning based on needs analysis and the exixtence of good synergies berween the central goverment and the provincial as well as local goverment, especialy the education office and the school the achievement of the 2013 curriculum implementation program for physical education subyects is goos, because in the activities of the learning activities process studen are more active.Keywords : Implementation of the 2013 Curriculum, Physical Education